Bots and botnets: An overview of characteristics, detection and challenges - Eslahi, M.; Salleh, R.; Anuar, N. B. (2012 IEEE International Conference on Control System, Computing and Engineering, 2012)
Recently, botnets have become the biggest threat to cyber security and have been used as an infrastructure to carry out nearly every type of cyber attack. They have a dynamic and flexible nature and the botmasters, who control them, update the bots and change their codes from day to day to avoid the current detection methods. In this paper, we present an overview of botnets' characteristics along with their malicious activities. We also review the current botnet detection methods in addition to their advantages and disadvantages. Finally we discuss the new generation of botnets on cloud and mobile environments.